Sistem Informasi Manajemen Pengolahan Data Bahan Bakar Minyak (BBM) Solar Berbasis Laravel Pada PT. Bukit Intan Manunggal - Maslianor; Veronika Anastasia Yohana Bella (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
A Laravel-based Diesel Fuel Data Processing Management Information System at PT. Bukit Intan Manunggal was developed to simplify the fuel management process by reducing recording time, minimizing data input errors, and providing accurate and informative reports for the company. This system is designed to significantly contribute to improving the efficiency and accuracy of diesel fuel management activities at PT. Bukit Intan Manunggal. Previously, the company faced several challenges in diesel fuel data processing, such as manual recording, data inconsistency, and delays in report generation, which affected operational effectiveness. Therefore, the design and implementation of a Laravel-based web system utilizing internet technology was considered necessary to streamline and optimize the management of diesel fuel data required by the company.The data collection methods used in this study include observation, interviews, and literature review to obtain accurate system requirements. The system design employed Unified Modeling Language (UML) and Entity Relationship Diagram (ERD) to model system processes and database structures. The programming languages and tools used in system development include PHP, XAMPP, MySQL, and CSS (Cascading Style Sheets). The results of this study indicate that the implemented system is able to improve data processing speed, reduce human error, and support better decision-making through reliable information, thereby enhancing overall operational performance.